Strategi pembelajaran Fiqih adaptif terhadap kurikulum merdeka di Madrasah - Indriany, Hafizah; Azwa, Nurul; Neni (Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze adaptive Fiqh learning strategies in relation to the implementation of the Merdeka Curriculum (Independent Curriculum) in Islamic schools (madrasahs). Using a qualitative approach through library research, the data were obtained from textbooks, journal articles, research reports, and relevant educational policy documents. The findings indicate that adaptive Fiqh learning strategies must align with the core principles of the Merdeka Curriculum, including differentiated instruction, project-based learning for strengthening the Pancasila and Rahmatan lil ‘Alamin student profiles (P5RA), and self-regulated learning. Adaptive Fiqh learning emphasizes not only the mastery of Islamic jurisprudence but also the development of students’ character, spirituality, and social awareness. Fiqh teachers play a key role as facilitators, innovators, and role models in fostering contextual, collaborative, and reflective learning. This adaptation is expected to enhance the relevance of Fiqh education to contemporary challenges and strengthen the role of madrasahs in shaping religious, critical, and globally competitive learners.